2008
DOI: 10.1111/j.1476-5381.2008.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

A standardized extract of Ginkgo biloba suppresses doxorubicin‐induced oxidative stress and p53‐mediated mitochondrial apoptosis in rat testes

Abstract: Background and purpose: Doxorubicin evokes oxidative stress and precipitates cell apoptosis in testicular tissues. The aim of this study was to investigate whether the Ginkgo biloba extract 761 (EGb), a widely used herbal medicine with potent anti-oxidant and anti-apoptotic properties, could protect testes from such doxorubicin injury. Experimental approach: Sprague-Dawley male rats (8 weeks old) were given vehicle, doxorubicin alone (3 mg kg -1 every 2 days for three doses), EGb alone (5 mg kg -1 every 2 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
72
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 44 publications
14
72
0
3
Order By: Relevance
“…KLF6 mediates apoptosis in the setting of ADR treatment. ADR has been previously shown to activate intrinsic apoptotic pathways in other models of tissue injury (18)(19)(20); we showed that a loss of KLF6 increased the susceptibility to ADR-induced mitochondrial injury. Therefore, we hypothesized that a loss of KLF6 would result in the activation of intrinsic apoptotic pathways with ADR treatment.…”
Section: Klf6 Expression Is Reduced In Hiv-1 Transgenic Micementioning
confidence: 56%
See 1 more Smart Citation
“…KLF6 mediates apoptosis in the setting of ADR treatment. ADR has been previously shown to activate intrinsic apoptotic pathways in other models of tissue injury (18)(19)(20); we showed that a loss of KLF6 increased the susceptibility to ADR-induced mitochondrial injury. Therefore, we hypothesized that a loss of KLF6 would result in the activation of intrinsic apoptotic pathways with ADR treatment.…”
Section: Klf6 Expression Is Reduced In Hiv-1 Transgenic Micementioning
confidence: 56%
“…Nonetheless, we recognize that KLF6 may also regulate other genes involved in the activation of the intrinsic apoptotic pathway and mitochondrial injury. Although ADR has typically been observed to activate the intrinsic apoptotic pathway leading to tissue damage (19,20), the potential crosstalk between the extrinsic and intrinsic pathway in the setting of KLF6 depletion has to be further explored. Future studies will also need to determine the interaction between KLF6 and protein kinase, DNA-activated, catalytic peptide (PRKDC), a mice were treated with ADR at 12 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…Two major pathways involved in the process have been investigated in great depth (Gustafsson and Gottlieb 2007). As p53 responds to both DNA damage and oxidative stress to trigger downstream apoptotic signalling, the mechanism for apoptosis seems to originate both from the pharmacological consequences of DNA injury and from oxidative stress (Yeh et al 2009;Zhou et al 2012). In this study, AHLE induced reduced expression of Bcl-2, Bcl-xl and greater expression of Bax.…”
Section: Discussionmentioning
confidence: 70%
“…However, there were experimental studies which showed protective effects of GBE against testicular damage of many substances and other injuries: doxorubicin (Yeh et al, 2009), cadmium (Predes et al, 2011), cisplatin (Amin et al, 2012), diethylstilbestrol (Wang et al, 2008), carbon tetrachloride (Chávez-Moralez et al, 2010), testicular torsion/detorsion (Kanter, 2011). In addition, Taepongsorat et al (2008) showed that quercetin, one of the main components of GBE, ameliorated reproductive parameters such as motility, vitality and sperm concentration, and increased testicular weight in rats.…”
Section: Introductionmentioning
confidence: 99%